Long non‐coding RNA H19 promotes TDRG1 expression and cisplatin resistance by sequestering miRNA‐106b‐5p in seminoma. (14th November 2018) - Wei, Jingchao; Gan, Yu; Peng, Dongyi; Jiang, Xianzhen; Kitazawa, Riko; Xiang, Yali; Dai, Yingbo; Tang, Yuxin; Yang, Jianfu
Abstract: The role of TDRG1 in tumorigenesis and the progression of seminoma, as well as its role in regulating chemosensitivity of seminoma to cisplatin through the PI3K/Akt/mTOR signaling pathway, has been previously defined. However, the detailed mechanism underlying TDRG1 expression and concomitant chemoresistance conditions are unknown. Furthermore, it has been reported that non‐protein‐coding RNAs play an important role in a variety of vital processes including cellular chemosensitivity. However, the role of non‐protein‐coding RNAs in regulating the chemosensitivity of seminoma remains unknown. In this study, using microarray analysis, we found that long non‐coding RNA H19 was upregulated while miRNA‐106b‐5p was downregulated in an established cisplatin‐resistant TCam‐2 cell line. Moreover, H19 acts as a miRNA‐106b‐5p sponge and thus impairs the function of miRNA‐106b‐5p on its target gene, TDRG1. Based on these findings, we propose that H19 promotes the expression of TDRG1 by sequestering miRNA‐106b‐5p and uses this mechanism to facilitate cell survival in cisplatin‐based chemotherapeutic conditions. These findings elucidate the mechanisms, at least partially, applied to deregulate TDRG1 and cisplatin sensitivity, and may provide new therapeutic possibilities for chemoresistant seminoma. Abstract : Long non‐coding RNA H19 promotes the expression of TDRG1 through sequestering miRNA‐106b‐5p, and thus facilitates cell resistance to cisplatin in seminoma. The newly identified H19/miRNA‐106b‐5p/TDRG1 axis may serve as a potential target for the treatment of seminoma and the cisplatin‐resistant tumors.